Physical Chemical Treatment Of Stabilized Leachate Using Limestone, Activated Carbon And Zeolite - Foul, Ahmed El-Arabi Mohammed Abu (2007)
Leachate generated from Larut Matang landfill in Taiping was characterized. Colour, COD, iron and ammoniacal nitrogen were found to be high. The potential use of activated carbon, limestone and zeolite and their possible mixtures as an adsorbent was investigated in this research. Influence of shaking speed and contact time was studied. The adsorption isotherms and the kinetics constants were determined. The batch experiments demonstrated that both combine mixtures of activated carbon with zeolite at 15:25 (by volume) and activated carbon with limestone and zeolite at 15:10:15 (by volume) gave the best results with removal efficiencies more than 90% for colour and ironi 85% for COD, 80% for ammoniacal nitrogen at shaking speed of 350 rpm and contact time of 4 hours. Both Langmuir and Freundlich isotherms fitted well to the experimental data with correlation coefficient more than 93%. The mixtures yielded adsorption capacity of 522.19, 232.56, 52.63, 21.01 (mg/g) and SOO, 200, 50, 20.20 (mg/g) for colour, COD, iron and ammoniacal nitrogen, respectively. The kinetic results showed that the data fitted well with the pseudo second order equation with correlation approaching unity for all parameters in all experiments implying that the rate limiting step may be chemisorption. The regeneration experiments showed that 0.2 M HN03 can be used to regenerate activate carbon and 0.2 M HCI and NaCI mixture and regenerate zeolite, with regeneration more than 80% in most cases.